A BLOCKCHAIN-BASED ONLINE REVIEW SYSTEM OF TOURISM PRODUCTS USING ETHEREUM - Rizal, Mohamad Rafi Raihan (Jurnal Techno Nusa Mandiri, 2021)
Rapid technological advances have made blockchain technology applicable not only to digital money, but in various fields. One of the areas that can be implemented by blockchain is digital tourism, specifically in the online review system of tourism products. The current online review system has several problems due to its centralized nature. The problem faced is the manipulation of review data which can be in the form of review deletion by a centralized party. This research proposes a decentralized online review system using the Ethereum blockchain technology, Smart Contracts, and IPFS to provide a secure, transparent, and trustworthy online review system platform. The purpose of this research is to implement a permission-less blockchain as a storage for reviews (review forms and log notes) and develop a web application as a user interface. The data used is data from travel sites which contain details about hotels and restaurants in Bukhara. The results displayed are the development of a web application that implements a permission-less blockchain using Ethereum and the system performance is displayed based on system testing, which comprised of unit testing and Black-Box testing.